2012
DOI: 10.1111/papr.12003
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐term Efficacy and Safety of Percutaneous Cervical Nucleoplasty in Patients with a Contained Herniated Disk

Abstract: These results show long-term effectiveness and safety of PCN in patients with a one-level contained cervical herniated disk, and the reliance of selecting patients meeting ideal criteria for successful PCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Recently, experience with advanced endoscopic cervical surgery allows for removal of small uncovertebral spurs and performance of interbody fusion [15]. However, fusion often occurs with some disc space narrowing, especially if the endplates have been debrided, compared to the slight widening due to the interbody spacer with an interbody fusion [16-17]. Minimal cervical discectomy with endplate debridement increases the fusion rate [14-15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experience with advanced endoscopic cervical surgery allows for removal of small uncovertebral spurs and performance of interbody fusion [15]. However, fusion often occurs with some disc space narrowing, especially if the endplates have been debrided, compared to the slight widening due to the interbody spacer with an interbody fusion [16-17]. Minimal cervical discectomy with endplate debridement increases the fusion rate [14-15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated PCN to be both safe and effective. [ 14 15 17 18 ] In our study of 980 nm diode laser device was used spherical kneading called plasma. In probe device through the skin and under the Centre for Adverse Reactions Monitoring…”
Section: Methodsmentioning
confidence: 99%
“…Facet joints, discs, and sacroiliac joints are proven sources of chronic spinal pain and are accessible to neural blockade . Removal or correction of structural abnormalities of the spine may fail to cure and may even worsen painful spinal conditions (3,82,139,177,195,196,202,207,232,260,261,295,(367)(368)(369)(370)(371)(372)(373)(374). The degenerative processes of the spine and the origin of spinal pain are complex without correlation of radiographic changes to the clinical picture and prognosis (8,.…”
Section: Therapeutic Interventional Techniquesmentioning
confidence: 99%